The role of the guiding media discourse for the Iraqi media in supporting the education process during the crises (Journal of the College of Basic Education, 2022)
The aim of the research is to know the role of the guiding media discourse for the Iraqi media in supporting the education process during the crises. The research used the descriptive analytical method, by (questionnaire), and selected 74 items.so the results as following: the first rank was (The means of the Iraqi guiding media discourse, the most followed by the audience, in supporting the educational process during crises with mean 3.81, The second, rank was (the importance of the guiding media discourse in the Iraqi media in supporting the educational process during crises) with mean 3.37. The third rank was the scientific skills used by the guiding media discourse in supporting the educational process during crises (The scientific skills used by the guiding media discourse in supporting the educational process during crises) with mean 3.15. The fourth rank was (The degree of credibility, objectivity and accuracy of the guiding media discourse in the Iraqi media in supporting the educational process during crises) with mean 3.05